Model Kontekstual Perencanaan Pembangunan Daerah: Studi Kasus Provinsi Papua - Andry, Andry; Silo, Akbar; Hafizrianda, Yundi; Musa'ad, Muhammad (JURNAL EKOLOGI BIROKRASI, 2022)
This study aims to identify and analyze the orientation of meeting the basic socioeconomic needs of the community with the context of Papua, determine and analyze the contextual model of regional development planning in Papua Province, the factors that determine the success of implementing the contextual model of regional development planning in Papua. This study uses a qualitative descriptive method and leads to a case study approach. The data collection method used in-depth interview techniques, content analysis, and Focus Group Discussion (FGD). The results show that development planning must be based on the local context of Papua. What is done by the Government is to build public awareness of the importance of implementing government programs such as in terms of health. Health needs to be monitored from the perspective of the behavior of the Papuan people, namely from cleanliness, fulfillment of nutrition, and fulfillment of basic immunizations. However, the good intentions of this government are considered bad by the Papuan people so that the contextual implementation of this development requires the role of traditional leaders, religious leaders, officials in the village so that the development of the Papua Province is in accordance with a contextual model based on the aspirations of the people in the Papua Province.